2016
DOI: 10.3847/0004-637x/820/1/29
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in the Shadows. Ii. Collisional Dust as Exoplanet Markers

Abstract: Observations of the youngest planets (∼1-10 Myr for a transitional disk) will increase the accuracy of our planet formation models. Unfortunately, observations of such planets are challenging and time-consuming to undertake, even in ideal circumstances. Therefore, we propose the determination of a set of markers that can preselect promising exoplanet-hosting candidate disks. To this end, N-body simulations were conducted to investigate the effect of an embedded Jupiter-mass planet on the dynamics of the surrou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 66 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Compared to using the corotating gap opened by the planet as a diagnostic (Dobinson et al 2013(Dobinson et al , 2016, measuring variations in the dust emission near MMRs is much more subtle and requires much higher spatial resolution and sensitivity. As we have shown, the bump vs dip feature near the 2:1 MMR is marginally detectable with ALMA for the nearest protoplanetary discs, so long as the dust profile closely matches the collisional profile of the planetesimals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to using the corotating gap opened by the planet as a diagnostic (Dobinson et al 2013(Dobinson et al , 2016, measuring variations in the dust emission near MMRs is much more subtle and requires much higher spatial resolution and sensitivity. As we have shown, the bump vs dip feature near the 2:1 MMR is marginally detectable with ALMA for the nearest protoplanetary discs, so long as the dust profile closely matches the collisional profile of the planetesimals.…”
Section: Discussionmentioning
confidence: 99%
“…Dobinson et al (2013) showed that collisional dust that is generated near the gap opened by a giant planet in the inner regions of a transition disc should produce a distinct observable marker that could be used to infer the presence of the planet. In a followup study, it was found that morphological differences in the dust emission could be used to determine whether the planet had a circular or eccentric orbit (Dobinson et al 2016). Moreover, substructure due to mean-motion resonances (MMRs) with a giant planet may hold additional clues that could be used to constrain the properties of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, we have not included planetesimal formation or planet growth, though large bodies increase the velocity distributions of nearby objects, leading to more destructive collisions (e.g. Dobinson et al 2016). Our simulations only apply to young disks at the very beginning of disk evolution.…”
Section: Only Sticking and Fragmentation (Sf) Collision Outcomesmentioning
confidence: 99%
“…Because debris disks traditionally are associated with collisional erosion of planetsimals (a relatively slow process) they are generally treated as a steady state. Other dynamical activities such as extra perturbations due to newly formed planets or on-going planet accretion through collisions can also potentially produce additional source material for a dusty observable debris disk (Dobinson et al 2016). Particularly, most giant impacts are not perfect merging events even if they result in substantial growth of the tar-get.…”
Section: Introductionmentioning
confidence: 99%